2014
DOI: 10.1186/1476-511x-13-109
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus supplement alters postprandial lipemia of healthy male subjects: a pilot cross-over trial

Abstract: BackgroundEpidemiological studies have found a U-shaped relationship between serum phosphorus and cardiovascular disease (CVD). The mechanism(s) behind such a relationship are poorly understood. Phosphorus (P) is reported to improve insulin sensitivity, which is involved in lipid metabolism, and thus we were interested in determining the impact of phosphorus ingestion on postprandial lipemia, a recognized CVD risk factor.FindingsA within–subject study design was conducted, whereby 8 healthy male subjects recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
4
13
1
Order By: Relevance
“…PTH) are likely triggered and responding to the large P load in an attempt to return plasma P to normal. This somewhat mimics the response reported by Hazim et al, when healthy men ingested a 500mg inorganic P supplement with a high fat meal (23) . The sustained plasma P levels 6 hours postprandially make it distinctly possible that plasma P may still be elevated at the time of the next feed, potentially exposing the kidneys and other tissues to incrementally higher P concentrations with each meal, which may explain the adverse effects that were observed when these diets were fed to cats over prolonged periods (Alexander et al, submitted).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PTH) are likely triggered and responding to the large P load in an attempt to return plasma P to normal. This somewhat mimics the response reported by Hazim et al, when healthy men ingested a 500mg inorganic P supplement with a high fat meal (23) . The sustained plasma P levels 6 hours postprandially make it distinctly possible that plasma P may still be elevated at the time of the next feed, potentially exposing the kidneys and other tissues to incrementally higher P concentrations with each meal, which may explain the adverse effects that were observed when these diets were fed to cats over prolonged periods (Alexander et al, submitted).…”
Section: Discussionsupporting
confidence: 86%
“…Karp et al (2007) found similar trends in serum phosphate and urinary P excretion, when tripolyphosphate and monophosphate supplements were consumed (22) . Additionally, healthy male volunteers fed a 500mg P supplement showed that serum phosphate increased postprandially, while a transient decrease was apparent after a placebo (23) . Sustained increases in plasma P are thought to be harmful due to the physiological consequences associated with the regulation of plasma P (13) .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the results of the present series of studies add to the growing literature, suggesting that inclusion of added inorganic P in diets results in a dose-dependent increase in plasma P, with a concurrent elevation in PTH ( 26 , 29 ) . This relationship is far from straightforward, however, with a sustained postprandial elevation in plasma P apparent when diets with a Ca:P <1·0 were fed compared with that seen when the diet Ca:P was >1·5.…”
Section: Discussionsupporting
confidence: 72%
“…Karp et al ( 25 ) found similar trends in serum phosphate and urinary P excretion, when tripolyphosphate and monophosphate supplements were consumed. In addition, healthy male volunteers fed a 500 mg P supplement showed that serum phosphate increased postprandially, while a transient decrease was apparent after a placebo ( 26 ) . Sustained increases in plasma P are thought to be harmful due to the physiological consequences associated with the regulation of plasma P ( 14 ) .…”
mentioning
confidence: 99%
“…While major electrolytes were replaced, the displacement of dietary protein by refined constituents poses the added challenge of decreased intake of micronutrients including phosphorous [ 80 , 81 ]. Dietary phosphorous is of particular relevance to the results of the present study given recent reports identifying its roles in regulating body weight [ 82 ], energy metabolism [ 83 ], postprandial lipemia [ 84 ], and glucose tolerance [ 85 ], implicating a potential effect on adipose tissue. Whether the results observed in this study are a direct consequence of increased dietary fat or an indirect response to micronutrient deficiency triggered by the refined diet remains to be established in future research.…”
Section: Discussionmentioning
confidence: 96%